Beneficial cardiovascular effects of bariatric surgical and dietary weight loss in obesity. - Rider, O; Francis, J; Ali, M; Petersen, SE; Robinson, M; Robson, M; Byrne, J; Clarke, K; Neubauer, S (2009)
OBJECTIVES: We hypothesized that, in obese persons without comorbidities, cardiovascular responses to excess weight are reversible during weight loss by either bariatric surgery or diet. BACKGROUND: Obesity is associated with cardiac hypertrophy, diastolic dysfunction, and increased aortic stiffness, which are independent predictors of cardiovascular risk. METHODS: Thirty-seven obese (body mass index 40 +/- 8 kg/m(2)) and 20 normal-weight subjects (body mass index 21 +/- 2 kg/m(2)) without identifiable cardiac risk factors underwent cardiac magnetic resonance imaging for the assessment of the left and right ventricles and of indexes of aortic function. Thirty of the obese subjects underwent repeat imaging after 1 year of significant weight loss, achieved in 17 subjects by diet and in 13 subjects by bariatric surgery. Seven obese subjects underwent repeat imaging after 1 year of continued obesity. RESULTS: Left and right ventricular masses were significantly increased, left ventricular diastolic function impaired, and aortic distensibility reduced in the obese. Both diet and bariatric surgery led to comparable, significant decreases in left and right ventricular masses, end-diastolic volume, and diastolic dysfunction, and an increase in aortic distensibility at all levels of the aorta, most pronounced distally (e.g., distal descending aorta 5.1 +/- 1.8 mm Hg(-1) x 10(-3) before weight loss and 6.8 +/- 2.5 mm Hg(-1) x 10(-3) after weight loss; p < 0.001). No improvements were observed in continued obesity. CONCLUSIONS: Irrespective of method, 1 year of weight loss leads to partial regression of cardiac hypertrophy and to reversal of both diastolic dysfunction and aortic distensibility impairment. These findings provide a potential mechanism for the reduction in mortality seen with weight loss.